Technological modernity and terrorist propaganda: proposal of a discursive analysis to face the messages of terrorism in the digital age - ALARCÓN SÁNCHEZ, Ramón (Journal of the Spanish Institute for Strategic Studies, 2022)
Terrorism is a multidimensional phenomenon where communication, politics and the struggle for legitimacy play a decisive role. This paper tackles its study from several perspectives. Initially, it approaches the ontology of technological modernity, where ’the digital’ has colossal importance, and critically examines the phenomenology of this present, as well as its socio-political, economic and cultural implications. This creates a vantage point from which to observe the following sections from a better perspective, which examine terrorism from different positions and, finally, propose a discursive analysis that, by synthesizing the main psychosocial mechanisms used by terrorists in their propaganda, allows us to see their dialectical tricks. This is a fundamental support for the media and citizens in general, taking into account that the Internet makes it possible for terrorists to massively and globally distribute their messages.